Conference on implementation of anti‐oppressive practice into primary care: Activity report - Junki Mizumoto; Kota Sano; Takashi Ando; Aya Yumino; Maho Haseda; Gemmei Iizuka; Chinatsu Mukohara; Daisuke Nishioka; Yuko Takeda (Journal of General and Family Medicine)
Anti‐oppressive practice (AOP) provides a framework that challenges structural inequities and illuminates the lives of both patients and professionals. We introduce AOP into primary care in Japan.